1986
DOI: 10.1037/0278-7393.12.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Differential memory changes with age: Exact retrieval versus plausible inference.

Abstract: Elderly and college-age subjects were compared in two experiments, one involving episodic memory and one involving semantic memory. Responses were generally slower for older subjects; however, in some conditions, older subjects were as good as or better than young subjects, even in terms of response time. The results suggest that older subjects have no difficulty with memory tasks that do not require exact memory-matches or careful inspection of retrieved propositions. It is argued that careful inspection is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 40 publications
13
82
2
3
Order By: Relevance
“…Previous studies have also shown that when participants are asked to recall a story, younger adults' recall is often more reproductive and text based (using specific details), whereas older adults' recall is more reconstructive and interpretive (Adams, 1991;Adams, Smith, Nyquist, & Perlmutter, 1997). In fact, some have argued that there may be motivational or strategic differences between younger and older adults that could explain these different patterns of data (e.g., Perlmutter & Mitchell, 1982;Reder, Wible, & Martin, 1986). Similarly, with inference recall, it appears that older adults have a fairly good memory for inferences, whereas their recall of factual information is worse than younger adults' recall.…”
Section: Free Recallmentioning
confidence: 93%
“…Previous studies have also shown that when participants are asked to recall a story, younger adults' recall is often more reproductive and text based (using specific details), whereas older adults' recall is more reconstructive and interpretive (Adams, 1991;Adams, Smith, Nyquist, & Perlmutter, 1997). In fact, some have argued that there may be motivational or strategic differences between younger and older adults that could explain these different patterns of data (e.g., Perlmutter & Mitchell, 1982;Reder, Wible, & Martin, 1986). Similarly, with inference recall, it appears that older adults have a fairly good memory for inferences, whereas their recall of factual information is worse than younger adults' recall.…”
Section: Free Recallmentioning
confidence: 93%
“…There is also evidence to suggest that older adults rely on more gist-based memory, which refers to a highly abstracted and semantically rich representation of the past, relative to more specific verbatim memory, which is memory for the exact sensory inputs of a given situation in the past (e.g., Reder et al, 1986). Fuzzy-trace theory (Brainerd & Reyna, 2001) suggests that with age the ability to retain verbatim information deteriorates more quickly than the ability to retain gist information (e.g., Schacter, Koutstaal, Johnson, Gross, & Angell, 1997;Titcomb & Reyna, 1995;Tun, Wingfield, Rosen, & Blanchard, 1998).…”
Section: O R R E C T E D P R O O F E False Memory and Flexible Remmentioning
confidence: 99%
“…Information that is represented in a specific form can then support recollection at retrieval, resulting in a more precise grain size and highly accurate remembering. However, older adults typically draw on information from gist-based representations, which can be then supplemented with prior knowledge and inferences (see Reder, Wible, & Martin, 1986)-sometimes leading to specific and predictable memory errors that are consistent with prior knowledge. Gist-based processing typically leads to familiarity at retrieval, translating to somewhat less …”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Las personas mayores son más proclives que los jóvenes a basar sus decisiones de reconocimiento en la familiaridad o plausibilidad de la información (Reder et al, 1986) y en los conocimientos previos (García-Bajos et al, en revisión; Mather et al, 1999) y, por lo tanto, esta predisposición a depender de la memoria semántica también podría estar implicada en su menor capacidad para la atribución de la fuente.…”
Section: Discussionunclassified
“…Estas dificultades podrían acentuarse en las personas mayores que, normal-mente, presentan una menor resistencia a la interferencia (Benedet, Martínez-Arias y Alejandre, 1998) y, en algunos casos, son cognitivamente menos rápidas, disponen de menos recursos atencionales y procesan la información de una forma más automática que los jóvenes (Park et al, 2002). Como resultado, por ejemplo, las personas mayores tienden a depender de la tipicidad o de la familiaridad de la información en mayor medida que los jóvenes, por lo que su probabilidad de aceptar contenidos falsos típicos es también mayor (García-Bajos, Migueles y Aizpurua, en revisión; Mather, Johnson y De Leonardis, 1999;Reder, Wible y Martin, 1986).…”
Section: Introductionunclassified